2012
DOI: 10.1016/j.neurobiolaging.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

FUS mutations in sporadic amyotrophic lateral sclerosis: Clinical and genetic analysis

Abstract: Fused in sarcoma (FUS) or translocation in liposarcoma (TLS), a DNA/RNA-binding protein, causes a dominant autosomal inherited form of amyotrophic lateral sclerosis (ALS), ALS 6. Its main role in neurodegeneration is highlighted by the presence of cytoplasmic accumulation of its mutant protein form in ALS patients. To further define the frequency and spectrum of FUS gene mutations, we have performed a molecular screening of a cohort of 327 Italian patients from Southern Italy with sporadic ALS (SALS). We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 20 publications
(28 reference statements)
2
11
1
Order By: Relevance
“…Therefore, we speculate that the high signal intensities of the corticospinal tracts on the DWI image in the present case reflect a rapid degeneration of the UMN and the corticospinal tracts, which is not a common finding in ALS cases with an FUS gene mutation. No specific findings, including abnormal signal intensities of the corticospinal tracts, have been reported on cerebral MRI of ALS cases with an FUS gene mutation (8,24,27). The present case also exhibited mild frontal lobe atrophy on MRI, as well as reduced cerebral blood flow in the bilateral frontal lobe areas according to the 99m Tc-ECD SPECT analysis.…”
Section: Discussionmentioning
confidence: 42%
“…Therefore, we speculate that the high signal intensities of the corticospinal tracts on the DWI image in the present case reflect a rapid degeneration of the UMN and the corticospinal tracts, which is not a common finding in ALS cases with an FUS gene mutation. No specific findings, including abnormal signal intensities of the corticospinal tracts, have been reported on cerebral MRI of ALS cases with an FUS gene mutation (8,24,27). The present case also exhibited mild frontal lobe atrophy on MRI, as well as reduced cerebral blood flow in the bilateral frontal lobe areas according to the 99m Tc-ECD SPECT analysis.…”
Section: Discussionmentioning
confidence: 42%
“…Although FUS mutations were not found in sALS patients, this is probably due to both the selective detection of exons in mutational hotspot regions and the use of small sample sizes. Zou ZY reported that FUS mutations could be present in approximately 1.0% of northern Chinese sALS patients, which is similar to the 1.6% mutation frequency found in Korean patients and the 1.25% mutation frequency found Italian patients12141920. With regards to the frequency of TARDBP mutation, it appears that the frequency of TARDBP mutations in Caucasian populations (Italy: 2.7%; France and Quebec: 4.5%) was higher than that in Asian populations21222324.…”
Section: Discussionmentioning
confidence: 60%
“…The first two reports suggested that FUS mutations might only be associated with FALS [Kwiatkowski et al, ; Vance et al, ]. However, several recent reports identified FUS mutations in SALS patients, including the most common variants p.R521C and p.R521H (Table ) [Belzil et al, ; Blair et al, ; Broustal et al, ; Chiò et al, ; Corrado et al, ; Drepper et al, ; Groen et al, ; Kwiatkowski et al, ; Lai et al, ; Millecamps et al, ; Rademakers et al, ; Sproviero et al, ; Suzuki et al, ; Syriani et al, ; Ticozzi et al, ; Tsai et al, ; van Blitterswijk et al, ; Vance et al, ; Van Damme et al, ; Van Langenhove et al, ; Yamamoto‐Watanabe et al, ; Yan et al, ; Zou et al, ].…”
Section: Fus Mutations In Alsmentioning
confidence: 99%